Proposta de uma sequência didática para o estudo dos transgênicos a partir da abordagem CTS - Oliveira, Jonise Marques de (2021)
This research aimed to present and evaluate a didactic sequence proposal, centered on the transgenic theme, pointing out the contributions of the use of the Science, Technology and Society approach to the teaching of Sciences in Basic Education. In this sense, the guiding question of the research is: how is the STS approach used by teachers in the field of Natural Sciences? To elucidate the guiding question, the research intended to use theoretical assumptions that can contribute to the realization of teaching of a more reflective nature, developing a didactic sequence, planned in the theoretical-methodological molds, organized according to the objectives that the teacher wants to achieve, bringing content closer to students’ daily lives. The didactic sequence is elaborated through a set of activities connected with each other, with strategies and plans for determining each stage and/or activity, developing interconnected disciplinary contents, proposing improvement in the teaching and learning process. The didactic proposal was carried out with eight teachers in the area of Natural Sciences at the Professor Heliodoro Capistrano da Silva State School, Municipality of Cuiabá - MT. The research approach was based on the qualitative method, with the development of descriptive research. The data collection for this research took place in three stages: i) bibliographic research; ii) application of a questionnaire referring to personal, academic, professional and didactic-pedagogical actions of teachers; iii) evaluation of the didactic sequence by the participants through the application of a questionnaire. From the results obtained in this research, it was possible to verify that the teachers understand the importance of debating themes related to STS in Science teaching, however they show a weakness or a limitation in the understanding or, still, of how these themes can be added to the school practices. In order to share the study developed with other teachers, as a final product of this work, a didactic Guide was prepared containing the proposed didactic sequence. The results obtained indicated that the activities developed contribute to the process of teaching and learning about transgenics thematic and to the teaching of Sciences, with a real possibility of understanding scientific knowledge in line with STS issues.